A new species and first record of Cotinis Burmeister (Coleoptera: Scarabaeidae: Cetoniinae) for Venezuela - Gasca-Álvarez, Héctor Jaime; Deloya, Cuauhtémoc (Zootaxa, 2015)
A new Cotinis Burmeister (Coleoptera: Scarabaeidae: Cetoniinae: Gymnetini) species from Venezuela is described and illustrated. The new species is compared with Cotinis barthelemyi (Gory & Percheron) from Colombia. The Neotropical distribution of Cotinis is expanded to Venezuela. A revised key to the species of Cotinis is provided in both English and Spanish.